Assay-Based Differentiation in the Neutralization Profile of Unfractionated Heparin, Enoxaparin, and Fondaparinux by Andexanet Alfa. (8th January 2020) - Siddiqui, Fakiha; Tafur, Alfonso; Bontekoe, Emily; Iqbal, Omer; Jeske, Walter; Mehrotra, Siddharth; Hoppensteadt, Debra; Ramacciotti, Eduardo; Fareed, Jawed
Andexanet alfa is a recombinant factor Xa decoy protein, designed to reverse bleeding associated with oral anti-Xa agents. Andexanet alfa is also reported to neutralize the effects of heparin-related drugs. This study focused on the neutralization profiles of unfractionated heparin (UFH), enoxaparin, and, a chemically synthetic pentasaccharide, fondaparinux by andexanet alfa. Whole blood clotting studies were carried out using thromboelastography (TEG) and activated clotting time (ACT). The anticoagulant profile of UFH, enoxaparin, and fondaparinux was studied using the activated partial thromboplastin time (aPTT), thrombin time (TT), and amidolytic anti-Xa, and anti-IIa methods. Thrombin generation inhibition was studied using the calibrated automated thrombogram system. Reversal of each of these agents was studied by supplementing andexanet alfa at 100 µg/mL. In the TEG, andexanet alfa produced almost a complete reversal of the anticoagulant effects of UFH and enoxaparin; however, it augmented the effects of fondaparinux. In the ACT, aPTT, and TT, UFH produced strong anticoagulant effects that were almost completely neutralized by andexanet alfa. Enoxaparin produced milder anticoagulant responses that were partially neutralized, whereas fondaparinux did not produce any sizeable effects. In the anti-Xa and anti-IIa assays, UFH exhibited partial neutralization whereas enoxaparin and fondaparinux did not show any neutralization. All agents produced varying degrees of the inhibition of thrombin generation, which were differentially neutralized by andexanet alfa. These results indicate that andexanet alfa is capable of differentially neutralizing anticoagulant and antiprotease effects of UFH and enoxaparin in an assay-dependent manner. However, andexanet alfa is incapable of neutralizing the anti-Xa effects of fondaparinux.